Mihai Sin – suprafețele prozei - Nicoleta Sălcudeanu (Revista de Istorie și Teorie Literară)
The author clings from the very beginning to the substance of the harmlesss immediacy. Inside the benign, daytime writing, expressed through small, seemingly insignificant gesture, it is revealed, exasperatingly and unsettling slowly, the hideous figure of the absolute evil, it is revealed the bordering hell, the hell itself, on the line where the fragile human faces its intrinsically evil, but also its infernal otherness. Without any irony, but with the addition of substantial steel lucidity, the writing of Mihai Sin is a frowning aspect of French moralism, a mix of prose, essays and pamphlets, and vision is that of an angry Candide, a Candide obviously more skeptical than Voltaire himself. The great stake is actually the moral manifesto, ultimate and realistic at the same time. It’s about death, about all its forms, from the individual to that of an entire world.